The change of religion and the names - Kousgård Sørensen, John (Scripta Instituti Donneriani Aboensis, 1990)
What actually happened at the time when Denmark was christianized? An important viewpoint to the topic is the nomenclature, both personal names and place-names. What happened to these in the missionary period? Can they be exploited as evidence about the change of religion? What happened to these and to the naming practices in connection with the introduction of Christianity? These questions are relevant, because several pre-Christian cultic words entered into the personal nomenclature which the Christian mission found in use on its arrival. The fate of the nomenclature in the period does suggest that the change in religion took place reasonably peacefully and gradually. There are, however, certain features about the place-names suggesting that there were local differences in the conduct of the mission.